PacBio Amplicon Sequencing Method To Measure Pilin Antigenic Variation Frequencies of Neisseria gonorrhoeae - Egon A. Ozer (American Society for Microbiology, 2019)
ABSTRACT Gene diversification is a common mechanism pathogens use to alter surface structures to aid in immune avoidance. Neisseria gonorrhoeae uses a gene conversion-based diversification system to alter the primary sequence of the gene encoding the major subunit of the pilus, pilE. Antigenic variation occurs when one of the nonexpressed 19 silent copies donates part of its DNA sequence to pilE. We have developed a method using Pacific Biosciences (PacBio) amplicon sequencing and custom software to determine pilin antigenic variation frequencies. The program analyzes 37 variable regions across the strain FA1090 1-81-S2 pilE gene and can be modified to determine sequence variation from other starting pilE sequences or other diversity generation systems. Using this method, we measured pilin antigenic variation frequencies for various derivatives of strain FA1090 and showed we can also analyze pilin antigenic variation frequencies during macrophage infection. IMPORTANCE Diversity generation systems are used by many unicellular organism to provide subpopulations of cell with different properties that are available when needed. We have developed a method using the PacBio DNA sequencing technology and a custom computer program to analyze the pilin antigenic variation system of the organism that is the sole cause of the sexually transmitted infection, gonorrhea.